Quantitative analysis of social and financial market development - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2022)
This 30th volume of the International Symposia in Economic Theory and Econometrics explores the latest social and financial developments across Asian markets. Chapters cover a range of topics such as the impact of COVID-19 related events in Southeast Asia along the determinants of capital structure before and during the pandemic; the influence of new distribution concepts on macro and micro economic levels; as well as the effects of long-term cross-currency basis swaps on government bonds. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as real earnings impact and the effects of public policy. Together, Quantitative Analysis of Social and Financial Market Development is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.